Pendidikan Ramah Anak di Lingkungan Keluarga dalam Surah Al-Baqarah Ayat 133 - Ma'arif, Moh. Samsul; Nisa', Luthfatun; Ilham Ali Hasan (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
This research aims to examine how the concept of child-friendly education can be applied within the family environment based on the guidance found in Surah Al-Baqarah verse 133. Child-friendly education is an approach that prioritizes the well-being and development of children, creating a safe, supportive environment that facilitates their maximum potential. In Islam, the family plays a vital role in shaping the character and fundamental values of children. The research methodology used is al-tafsir al-maudhu'i, which begins by inventorying the Quranic verses on the importance of child-friendly education within the family. Child-friendly education in the family can be implemented through: 1) Balanced communication between parents and children; 2) The application of non-violent discipline; and 3) The development of positive character in children. Its relevance to children's education includes the value system, caregiving functions, learning materials, and teaching methodologies. The usefulness of this research lies in providing a positive contribution to the concept of early childhood education, serving as a guide for educating children to become righteous and morally upright, creating a harmonious family, and fostering love and affection.